Morphology-tunable synthesis and formation mechanism of SnO2 particles and their application in Ag–SnO2 electrical contact materials. Issue 5 (1st March 2022) - Lin, Zhijie; Liang, Yucang; Zeng, Yiming; Chen, Xuan; Liu, Manmen; Dai, Pinqing; Chen, Jialin; Sun, Xudong
Abstract: SnO2 powders with four distinct morphologies of prismoids, hollow rhomboidal tubes, solid rhomboidal rods, and needles have been prepared through morphology-conserved transformation from SnC2 O4 precursors. The SnC2 O4 precursors were synthesized by a facile oxalate precipitation method. A controllable periodic bond chain (PBC) growth was found to be critical for the formation of these SnC2 O4 samples. In the case of forward titration, SnC2 O4 prismoids were generated because the formed Sn3 O(OH)2 SO4 was attached on { 1 - 01} polar facets and inhibited the PBC growth along the c axis. By contrast, in the case of reverse titration, SnC2 O4 samples preferably formed one-dimensional shapes. Dissolution and ripening were observed during the formation of hollow tubes in the case of low molar ratio of Sn 2+ to C2 O4 2− . Further, the formation of SnC2 O4 needles was ascribed to the selective coordination of polyvinylpyrrolidone (PVP) on the side surface. The as-prepared SnO2 powders were used as reinforcement of Ag–SnO2 electrical contact materials, and a good adhesion was observed at the Ag (111)/SnO2 (200) interface. Further, the characterization results revealed that the sample reinforced by SnO2 tubes (with one-dimensional shape and hollow structure) had the lowest degradation rate under cathode arc erosion, which might be attributed to its good resistance to the dual action (heat and force) of cathode arc.